تحليل خصائص التحول اللغوي والتخليط اللغوي في كلمات صلوات "محمد ميمانغ سمبورنا" من قبل فرقة حضرة المحبة والي سونغو سيتوبوندو - Royhanah, Royhanah; Arifah, Nurdiana; Binti Mohamed, Yuslina (Journal of Arabic Language Teaching, 2024)
Hadrah al-Mahabah Wali Songo is a form of traditional Islamic art with a unique characteristic. Its uniqueness lies in the lyrics of the salawat or syi'iran that are performed, which differ from the usual hadrah because they were composed directly by Kyai Kholil As'ad Samsul Arifin, the caretaker of the Walisongo Islamic boarding school in Situbondo. His compositions, which carry very profound meanings to praise the Prophet, have received very positive responses from the community. Researchers have found the phenomenon of code-switching and code-mixing in the salawat performed by the Hadrah al-Mahabah group. One example is in the lyrics of the salawat "Muhammad Memang Sempurna" ("Muhammad is indeed perfect"). Therefore, this study aims to critically analyze the occurrence of code-switching and code-mixing in the lyrics of the salawat "Muhammad Memang Sempurna" by the Hadrah al-Mahabah Walisongo group. Using qualitative descriptive research and text content analysis, the study found one type of code-switching and code-mixing in these lyrics. The causes for these linguistic phenomena are attributed to both internal and external factors.